Communication engagements in the planning and implementation of community service among the youth the case of student organization leaders in the University of the Philippines Los Banos - Chico, Mark Lester M. (2014)
In a dynamic, ever-changing landscape of communication engagements between and among people, the youth is an interesting sector to explore. This study analyzed how student organization leaders in the University of the Philippines Los Banos (UPLB) engaged in communication in the planning and implementation of their community service.

This descriptive case study involved a series of focus group discussions (FGD) among 16 selected student leaders who were either organization or community service activity heads. Guided by the premises of Cybernetics and basic management functions, this study determined the different community service activities undertaken by UPLB students and analyzed the communication engagements in the management of their community service.

Around 203 community service activities per year were conducted by about 160 student organizations. These were predominantly welfare-related and these tried to address development concerns (e.g., education, employment, environment, health, nutrition, and child development). Their community partners included children, elders, students, out-of-school youth, teachers, other University constituents, abandoned people, villagers, and even members of other student organizations.
Keywords: Community service